2019
DOI: 10.1093/eurpub/ckz052
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer survival and comorbidities in lung cancer screening participants of the Gdańsk screening cohort

Abstract: Background In 2010, the World Health Organisation recommended implementation of screening programmes in four groups of diseases—neoplasms, cardiovascular diseases (CVD), diabetes mellitus (DM) and chronic obstructive pulmonary disease (COPD). It is due to the fact that they share the same, modifiable risk factors. Methods Between 2009 and 2011, 8637 heavy smokers (aged 50–75, smoking history >20 pack-years) were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Including these in a screening programme may improve cost-effectiveness, although quantifying such an improvement will require measurement of these potential added benefits. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including these in a screening programme may improve cost-effectiveness, although quantifying such an improvement will require measurement of these potential added benefits. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Including these in a screening programme may improve cost-effectiveness, although quantifying such an improvement will require measurement of these potential added benefits. 36 We investigated a number of objective measures of 'smoking damage' (FEV 1 /FVC ratio, CAC and presence of emphysema on CT), not included in the PLCO M2012 model, to see if they were independently predictive of lung cancer after controlling for PLCO risk score. The presence and degree of CAC remained an independent predictor of lung cancer.…”
Section: Lung Cancer Riskmentioning
confidence: 99%
“…Furthermore, the high CVC prevalence in this group suggests the possibility of using CAC to personalize cardiovascular risk more precisely. Data on comorbidity in LCS cohorts vary by country and population screened [25]. However, according to our results, they indicate a high cardiovascular risk [26,27] and increased mortality due to cardiovascular diseases [28].…”
Section: Discussionmentioning
confidence: 45%
“…In 8637 heavy smokers screened in the Pomeranian Pilot Lung Cancer Screening Program, 52% had cardiovascular disease (33 %), diabetes (26%), and COPD (21%). 141 A study that performed a "lung health check" during a lung cancer screening reported COPD in 57% of patients; 67% did not have a prior diagnosis. 142 Studies that incorporate spirometry into screening have similarly reported high incidences of previously undiagnosed COPD.…”
Section: Detection Of Comorbidities During Lung Cancer Screeningmentioning
confidence: 99%